2017
DOI: 10.3389/fphar.2017.00729
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Obstacles to Drug Repositioning in Japan

Abstract: Drug repositioning (DR) is the process of identifying new indications for existing drugs. DR usually focuses on drugs that have cleared phase-I safety trials but has yet to show efficacy for the intended indication. Therefore, DR can probably skip the preclinical and phase-I study, which can reduce the cost throughout drug development. However, the expensive phase-II/III trials are required to establish efficacy. The obstacles to DR include identification of new indications with a high success rate in clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, to promote DR in Japan, three Japanese pharmaceutical companies have started joint implementation of a drug discovery program, Joint Open INnovation of drUg repositioning (JOINUS), using a drug repositioning compound library constructed by these companies in 2017 (https://open-innovation-joinus.jp/joinus/). Nishimura et al described in detail the ongoing efforts to stimulate DR in Japan . Furthermore, the re–establishment of intellectual property for repositioned drugs may solve major problems of DR for practical use in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to promote DR in Japan, three Japanese pharmaceutical companies have started joint implementation of a drug discovery program, Joint Open INnovation of drUg repositioning (JOINUS), using a drug repositioning compound library constructed by these companies in 2017 (https://open-innovation-joinus.jp/joinus/). Nishimura et al described in detail the ongoing efforts to stimulate DR in Japan . Furthermore, the re–establishment of intellectual property for repositioned drugs may solve major problems of DR for practical use in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, DR can allow researchers to avoid carrying out preclinical tests and phase I trials, thereby reducing the cost of the drug development process (Figure ). Some estimates have suggested that DR requires an average of 6.5 years and US$300m dollars to approve and launch a drug …”
Section: Advantages Of Drug Repositioningmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Drug repositioning helps to curtail the drug development cost, which leads to an improvement in the economy of the treatment [15].…”
Section: Advantages Of Drug Repositioningmentioning
confidence: 99%
“…Because the candidate drugs have usually passed phase I safety trials, they can directly enter phase II/III safety/efficacy trials for the new indication, greatly reducing the cost and time associated with novel drug development. Drug repositioning has successfully identified therapies for various diseases, including Parkinson’s disease and dry eye [ 14 ], and has been aided by the concept of The Connectivity Map [ 15 , 16 ], which is based on the hypothesis that the mechanism of action of two drugs may be similar if they have similar gene expression signature (GES) and that a drug may be therapeutic if it elicits the opposite GES to that induced by the disease [ 17 , 18 ]. The data-driven approach has previously shown success when applied to drug repositioning [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%